2019
DOI: 10.1111/evo.13743
|View full text |Cite
|
Sign up to set email alerts
|

Testing the evolutionary constraints of metamorphosis: The ontogeny of head shape inTriturusnewts

Abstract: In vertebrates with complex, biphasic, life cycles, larvae have a distinct morphology and ecological preferences compared to metamorphosed juveniles and adults. In amphibians, abrupt and rapid metamorphic changes transform aquatic larvae to terrestrial juveniles. The main aim of this study is to test whether, relative to larval stages, metamorphosis (1) resets the pattern of variation between ontogenetic stages and species, (2) constrains intraspecific morphological variability, and (3) similar to the “hour‐gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…However if stages are not autonomous, structures that are required for different functions at different ontogenetic stages could be constrained in terms of their morphological evolution 25 . Thus, metamorphosis may either increase developmental canalization, leading to reduced morphological diversity in metamorphic forms, or it could reset the pattern of variation between larval and adult stages and allow greater morphological diversity across species 26 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However if stages are not autonomous, structures that are required for different functions at different ontogenetic stages could be constrained in terms of their morphological evolution 25 . Thus, metamorphosis may either increase developmental canalization, leading to reduced morphological diversity in metamorphic forms, or it could reset the pattern of variation between larval and adult stages and allow greater morphological diversity across species 26 .…”
mentioning
confidence: 99%
“…Ledbetter and Bonett 33 showed that limbs evolve faster and are less constrained for aquatic species (mostly paedomorphic) than terrestrial species (mostly direct-developing). Vučić, et al 26 demonstrated that metamorphosis cannot be regarded as a developmental constraint on the overall external head in a newt. Finally, Blankers, et al 34 hypothesized that developmental constraints on phenotype may limit morphological evolution to different microhabitats in plethodontids based on analysis of body and appendage lengths.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In natural unimodal hybrid populations, hybrids cannot be distinguished based on external morphology from parental species ( Arntzen et al, 2018 ). Additionally, it has been shown in the laboratory that values of tail shape, size and colouration patterns ( Vučić et al, 2018 ), as well as general head shape during larval development and after metamorphosis ( Vučić et al, 2019 ), are intermediate between hybrids and the parental species during ontogeny ( Vučić et al, 2019 ). Taking into account the aforementioned, we decided to use hybrid larvae (obtained from experimental crosses) to explore possible differences in cranial morphology due to different TH levels during larval development, since we were not interested in interspecific divergence at this point.…”
Section: Methodsmentioning
confidence: 99%
“…These two species have slightly different habitat preferences [22] and belong to different ecomorphotypes [23]. They show morphological differences at hatching, throughout larval development and after metamorphosis [24][25][26]. The larvae of the two species also differ in antioxidative response [27].…”
Section: Introductionmentioning
confidence: 99%